Procedural justice and responsiveness to psychological treatment of juvenile delinquents - López Escobar, Amelia Eréndida (Consorcio de Universidades Mexicanas A.C., 2014)
The aim of this research is to prove a structural model to analyze the relationship between procedural justice and the responsiveness to psychological treatment in juvenile delinquents. The sample were 92 adolescents who were sentenced by a juvenile court. Participants answered a questionnaire related to perception of the judicial procedure, treatment of the police, acceptation of the sentence and psychological treatment that received. Results revealed that of the adolescent positive perception of judge predicted the responsiveness of psychological treatment.